Cerebellar liponeurocytoma with atypical histological features – a rare example of a glioneuronal tumor - Hermann, Blanka; Woznica, Michal; Kloc, Wojciech; Borkowski, Piotr; Libionka, Witold; Izycka-Swieszewska, Ewa (Folia Neuropathologica, 2017)
We present a case of a rare neoplasm in a 77-year-old woman with previous oncological history, who developed a rapid onset of cerebellar symptoms. The neuroimaging detected a posterior fossa tumor suspected of meningioma which was completely resected soon after. Histologically the neoplasm had two components with different immunophenotype. One constituent was lobular, composed of monotonous mitotically active round cells with a predominant neuronal profile. The second, astrocytic component contained lipomatous cells intermixed with larger gemistocytic astrocytes. Fields of geographic necrosis as well as multifocal microvascular proliferation were observed. The Ki67 proliferation index was 12%. After two years of follow-up the patient remains free of symptoms and radiologic recurrence. The presented case of cerebellar liponeurocytoma is unusual in terms of its atypical histological features and prominent astrocytic component. The authors propose that the term ‘lipomatous glioneuronal tumor’ seems to be more appropriate for this type of lesion, considering its histologic spectrum and possible extracerebellar location.